Vivir la UCI: diferentes perspectivas - Lourdes Rubio Rico; María Jesús Aguarón García; María Ferrater Cubells; Dolors Toda Savall (Universidad de Alicante, 2012)
Being in an Intensive Care Unit may become a unique and often distressing experience for patines, relatives and professionals. This work aims to examine different people's experience in ICU and compiles statements from a patient, a relative and two nurses -one of which also offers another perspective from a relative who is a health professional too- in order to analyse the various experiences and identify common and different points. It intends to show the same fact affects people in different ways, harmonise the different versions and use these statements to improve identified deficencies and relieve the pressure of this experience.